2014
DOI: 10.1016/j.jns.2014.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production profiles in chronic relapsing–remitting experimental autoimmune encephalomyelitis: IFN-γ and TNF-α are important participants in the first attack but not in the relapse

Abstract: Multiple sclerosis (MS) is a chronic demyelinating disease often displaying a relapsing-remitting course of neurological manifestations that is mimicked by experimental autoimmune encephalomyelitis (EAE) in animal models of MS. In particular, NOD mice immunized with myelin oligodendrocyte glycoprotein peptide 35-55 develop chronic relapsing-remitting EAE (CREAE). To elucidate the mechanisms that cause MS relapse, we investigated the histopathology and cytokine production of spleen cells and mRNA expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
5
16
0
Order By: Relevance
“…Our results thus propose that the inhibition of S100B has a significant impact on the extent of neuroinflammatory features, and this appears in line with the typical clinical and neuropathological heterogeneity of the model [41,42]. Remarkably, the expression levels of IFNγ and TNFα are strongly decreased by the PTM treatment, in line with the notion that these two cytokines play a relevant role in the CNS, in both physiological and pathological conditions [43]. Conversely, IL-1β expression levels are not modulated by PTM.…”
Section: Discussionsupporting
confidence: 86%
“…Our results thus propose that the inhibition of S100B has a significant impact on the extent of neuroinflammatory features, and this appears in line with the typical clinical and neuropathological heterogeneity of the model [41,42]. Remarkably, the expression levels of IFNγ and TNFα are strongly decreased by the PTM treatment, in line with the notion that these two cytokines play a relevant role in the CNS, in both physiological and pathological conditions [43]. Conversely, IL-1β expression levels are not modulated by PTM.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed it was reported that an increase of IFN-γ production precedes relapse phases in MS patients. 33,34 Moreover, IFN-γ along with other type 1 cytokines, was proven to be augmented in CD4 + , CD8 + and CD14 + cells in MS patients undergoing disease reactivation, while they were normalized in stable patients or individuals undergoing IFN treatment. 35 In addition, it was also demonstrated that IFN-γ levels are upregulated during RR exacerbation phases, while IL-17 levels increase only in clinically isolated syndrome (CIS) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Remitting-Relapsing EAE (RR-EAE) induced by active immunization with the immunodominant epitope of MOG 35-55 is characterized by an initial acute phase, followed by a series of remissions and relapses phases [14]. The cytokine and chemokine profiles and the nature of cellular infiltrate are markedly different during the clinical course of RR-EAE, so that the maximal expressions of the pro-inflammatory cytokines IFN-c, IL-17 and TNF-a are important mediators for disease induction [15]. The specific Th2 cells for encephalitogenic peptides in CNS can inhibit Th1 autoimmune clones, presumably by secreting anti-inflammatory cytokine IL-4, IL-10, and TGF-b [16].…”
Section: Discussionmentioning
confidence: 99%